Civil-military cooperation in response to a complex emergency : just another drill? - Rietjens, S. J. H. (International studies in sociology and social anthropology ;, 2008)
Modern peace support operations are challenged by an array of issues that are not at all 'military' in nature. Increasingly, military and civilian actors like non-governmental organisations, ministries and contractors have to learn how to work together.